Choosing grammars to support language processing courses - Pereira, Maria João Varanda (2013)
Teaching Language Processing courses is a hard task. The level of abstraction inherent to some of the basic concepts in the area and the technical skills required to implement efficient processors are responsible for the number of students that do not learn the subject and do not succeed to finish the course. In this paper we intend to list the main concepts involved in Language Processing subject, and identify the skills required to learn them. In this context, it is feasible to identify the difficulties that lead students to fail. This enables us to suggest some pragmatic ways to overcome those troubles. We will focus on the grammars suitable to motivate students and help them to learn easily the basic concepts. After identifying the characteristics of such grammars, some examples are presented to make concrete and clear our proposal. The contribution of this paper is the systematic way we approach the process of teaching Language Processing courses towards a successful learning activity.